The association between benzodiazepines and asthma exacerbation, influenza-like illness related pneumonia and mortality: population-based studies using the United Kingdom Primary care data. - Nakafero, Georgina (2016)
Background: Influenza-like illness (ILI) and asthma are common diagnoses in the general practice and exert considerable morbidity and mortality worldwide. One potentially important strategy to reduce this is to determine whether commonly prescribed drugs modify the occurrence and outcomes of respiratory diseases including mortality. The benzodiazepines, a class of psychoactive drugs generally used in the treatment of anxiety and sleep disorders, have recently been suggested as having detrimental effects on immune response to infection, predisposing its users to increased risk of infection and mortality. These drugs have also been implicated in the pathogenesis of asthma. This thesis therefore aimed to investigate whether benzodiazepines modify the occurrence of asthma exacerbation and subsequent mortality in patients with asthma as well as ILI-related pneumonia and ILI-related mortality in patients with ILI.